Electrochemical treatment of leather industry wastewater - Halilović, Namir; Krdžalić, Edin; Bašić, Azra; Dacić, Minela; Avdić, Nurudin (Bulletin of Chemists and Technologists of Bosnia and Herzegovina, 2017)
Leather industry wastewater is contaminated with bacteria including Escherichia Coli. In this paper, results obtained from analysis of leather industry wastewater samples with use of copper electrodes are presented and compared with the results of use of aluminum electrodes and mixed metal oxide electrodes. In all experiments the same materials were used as anode and cathode except the two last where anode of the mixed metal oxides and steel cathode was used. Electrodes with platinum group metals or their oxides as active coatings are generally the best suited for electrochemical water disinfection. After 7 min of electrolysis at only 0,018 A/dm2, Cl- was reduced using both tested electrodes, the efficiency of microorganisms removal followed the order: Cu > Al. The electrochemical treatment of wastewater resulted in the production of chlorine gas and hypochlorite, which is microorganisms deactivator. Also, electrocoagulation by aluminum anode was used for water purification to reduce all pollutants, including chlorides and microorganisms.